Trina Solar : expanding to the United States - Chen, Zhiwu; Sudhir, K.; Elias, Jaan (London : SAGE Publications Ltd, 2017)
At the end of 2010, Jifan Gao, Trina Solars founder and chairman, wondered how his company could expand its presence in the United States market. In the previous five years, Trina, a company with manufacturing and headquarters in Changzhou, China, had managed to grow rapidly by selling photovoltaic (PV) modules in Europe. However, Trina lagged behind some of its Chinese rivals, such as Yingli and Suntech Power, in supplying modules to the United States. Gao had targeted the U.S. market in 2010, and Trina had increased its sales in the country during 2009. But other module makers were also expanding their presence in the United States. Trina had to decide how it was going to respond and how much it was willing to invest in its efforts to grow in the U.S.
Originally published: Chen, Z., Sudhir, K., & Elias, J. (2016). Trina Solar: Expanding to the United States. 10-041. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol10.cases.som.yale.edu/trina-solar.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Trina Solar; Solar energy industries -- China; Solar energy industries -- United States